36. PATIENT SATISFACTION WITH TRADITIONAL MEDICINE SERVICES AT THE DEPARTMENT OF TRADITIONAL MEDICINE, 175 MILITARY HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the patient satisfaction rate regarding traditional medicine services at the Department of Traditional Medicine, 175 Military Hospital in 2024 and identify associated factors.Methods: A cross-sectional descriptive study was conducted on 340 patients utilizing traditional medicine services at the Department of Traditional Medicine, 175 Military Hospital, from February 2024 to October 2024.Results: The overall satisfaction rate for traditional medicine services at the Department of Traditional Medicine was 85.59%. Patients reported the highest satisfaction rate in the aspect of service delivery outcomes at 82.06%, while the lowest satisfaction rate was in the transparency of information and medical examination and treatment procedures at 75.59%. Occupation and educational level were statistically significantly associated with patients' overall satisfaction in the study.Conclusion: Evaluating patient satisfaction provides an important basis for implementing appropriate interventions to ensure patient needs are met.
Keywords: Patient satisfaction; traditional medicine; 175 Military Hospital; 2024